Evidence for Higgs boson decays to a low-mass dilepton system and a photon in pp collisions at $\sqrt{s} =$ 13 TeV with the ATLAS detector - Fiolhais, M. C. N. (2021)
39 pages in total, author list starting page 23, 5 figures, 1 table, submitted to PLB, All figures including auxiliary figures are available at https://atlas.web.cern.ch/Atlas/GROUPS/PHYSICS/PAPERS/HIGG-2018-43/